2003
DOI: 10.1038/sj.eye.6700414
|View full text |Cite
|
Sign up to set email alerts
|

Visual perception during phacoemulsification cataract surgery under subtenons anaesthesia

Abstract: Aim The aim of this study was to record the subjective visual experience of patients during phacoemulsification and intraocular lens implantation under subtenons anaesthesia. Methods Prospective, nonrandomised, cohort, postoperative questionnaire based study. Patients selected underwent routine phacoemulsification and intraocular lens implantation under regional subtenons anaesthesia. v 2 and Fisher's exact tests (two-tail) were used to evaluate the data. Results A total of 104 patients were selected, 38 (36.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…Patient preference, however, is more complex than just these component parts. Other factors contribute to a greater or lesser extent, including aspects such as variation from preconceptions of the process, awareness during surgery and intra-operative visual perception [7]. Patient satisfaction is an important marker of quality of care but a difficult outcome to measure.…”
Section: Discussionmentioning
confidence: 99%
“…Patient preference, however, is more complex than just these component parts. Other factors contribute to a greater or lesser extent, including aspects such as variation from preconceptions of the process, awareness during surgery and intra-operative visual perception [7]. Patient satisfaction is an important marker of quality of care but a difficult outcome to measure.…”
Section: Discussionmentioning
confidence: 99%
“…Wickremasinghe SS et al found that although not statistically signifi cant, younger subjects (<65 years) tend to fi nd the visual experience more frightening than those over 80 years (35.7 versus 21.4%) 15 .…”
Section: Discussionmentioning
confidence: 97%
“…[10][11][12][13][14][15][16][17] We report that flashing lights and floaters are commonly experienced by patients immediately following an IVT injection, and that flashes are experienced by almost two-thirds of patients within the first 2 weeks following the procedure. Preinjection VA, clinical indication for the IVT injection, and the nature of the pharmacological agent injected did not influence the visual experiences of patients, although the authors concede that subgroups analysis was limited because of its small size.…”
Section: Discussionmentioning
confidence: 99%
“…3 Indeed, some authors are even using IVT therapeutic agents for relatively rare disorders, such as central serous chorioretinopathy. 3 Patients' visual perceptions and experiences induced by frequently performed ophthalmic surgical procedures, such as cataract surgery (under topical [10][11][12][13][14][15] and regional anesthesia [11][12][13][14]16,17 ), glaucoma filtration surgery, 18 and vitreoretinal surgery, [19][20][21][22] are well documented. Indeed, the beneficial effect of preoperative counseling with respect to known and anticipated visual experiences during phacoemulsification cataract surgery, under topical anesthesia, in terms of reducing patients' fear, has been described.…”
Section: Introductionmentioning
confidence: 99%